Spectrum of male lower urinary tract symptoms and erectile dysfunction at a tertiary care urology clinic: A prospective study - Balagobi, B.; Sarma, S.T.; Sripandurangana, S.; Gobishangar, S.; Bavani, S.; Jothini, T.; Shathana, P.; Thangarajah, B.R.; Coonghe, P.A.D.; Thanusan, V. (Sri Lanka Association of Urological Surgeons, 2024)
Introduction Lower Urinary Tract Symptoms (LUTS) significantly impact men's quality of life, often due to benign prostatic occlusion. Erectile dysfunction (ED) is also linked to LUTS. Therefore, the study was aimed to assess the severity of LUTS associated with demographic and clinical factors and ED, which is potential for tailored care and public health strategies to alleviate the burden on male patients. Methods This prospective cross-sectional study was conducted at a urological clinic in Teaching Hospital, Jaffna, for one-year, after obtained ethical approval. It involved male married patients who completed questionnaires on Lower Urinary Tract Symptoms (LUTS), International Prostate Symptoms Score (IPSS), and International Index of Erectile Function (IIEF), excluding those with catheters other penile pathologies. The study gathered demographic and clinical data through LUTS questionnaire, assessed LUTS severity using the IPSS scale and also considered quality of life (QoL) in relation to urinary symptoms. The IIEF questionnaire addressed erectile dysfunction. Data accuracy was ensured through patient self-reports and investigator interviews. Statistical analyses employed SPSS and included descriptive statistics and Pearson correlation. Multiple linear regression to explore the relationship between independent and the dependent variables. Results Among the 181 male participants, mean age and BMI were 66.5±8.6 years and 24.4 ± 4 kgm-2 respectively. The majority exhibited moderate to severe LUTS, primarily attributed to Benign Prostatic Occlusion (BPO). Erectile Dysfunction (ED) was prevalent in 28.7% of LUTS patients. With increasing in age and severity of LUTS degree of ED was higher. Pearson correlation analysis showed a positive correlation between LUTS severity and ED,QoL before treatment, but not after. Multiple linear regression revealed that age, occupation, and BMI significantly influenced LUTS severity, with age showing a marginal negative association, while occupation and QoL had significant positive effects. The degree of ED was highly correlated with diabetes mellitus(DM), Ischaemic heart disease(IHD)and hypertension(HT). Conclusion LUTS were common among men over 40. Benign Prostatic Occlusion (BPO) was a common cause, and nearly 29% of LUTS patients had Erectile Dysfunction (ED). Age, occupation, and Quality of Life (QoL) significantly influenced LUTS and ED severity. Severe LUTS associated with higher prevalence of ED. Severity of ED was associated with higher IPSS score and age. ED was highly correlated with Metabolic syndrome and severity of LUTS.
Keywords: Lower urinary tract symptoms; International prostate symptoms score; Quality of life; Erectile dysfunction